Recensiones - X. X.,; I. M. B.,; F. V. I.,; S. S.,; S. M. A.,; J. M. G.,; S. A., (ECA: Estudios Centroamericanos, 1973)
No hay resúmenes disponibles.ECA Estudios Centroamericanos, Vol. 28, No. 293-294, 1973: 209-220.